Changes in the protein fraction of Merluccius bilinearis muscle under lactic acid bacterial fermentation using a Lactobacillus Acidophilus starter culture (ESP) - Elizondo, Luis J. (1987)
The effect of lactic acid bacterial fermentation on the protein fraction of Merluccius bilinearis muscle was evaluated. The non-protein fraction increased progressively with corresponding decreases in the percentage protein (dry weight) indicating proteolytic activity during fermentation. Significant increases in the percentages of the amino acids cystine, isoleucine, phenylalanine and tyrosine were observed after two months of fermentation. Percentages of arginine decreased significantly after one week and again after two months of fermentation.